A review of technological and clinical aspects of robot-aided rehabilitation of upper-extremity after stroke. (18th May 2016) - Babaiasl, Mahdieh; Mahdioun, Seyyed Hamed; Jaryani, Poorya; Yazdani, Mojtaba
Abstract: Cerebrovascular accident (CVA) or stroke is one of the leading causes of disability and loss of motor function. Millions of people around the world are effected by it each year. Stroke results in disabled arm function. Restoration of arm function is essential to regaining activities of daily living (ADL). Along with traditional rehabilitation methods, robot-aided therapy has emerged in recent years. Robot-aided rehabilitation is more intensive, of longer duration and more repetitive. Using robots, repetitive dull exercises can turn into a more challenging and motivating tasks such as games. Besides, robots can provide a quantitative measure of the rehabilitation progress. This article overviews the terms used in robot-aided upper-limb rehabilitation. It continues by investigating the requirements for rehabilitation robots. Then the most outstanding works in robot-aided upper-limb rehabilitation and their control schemes have been investigated. The clinical outcomes of the built robots are also given that demonstrates the usability of these robots in real-life applications and their acceptance. This article summarizes a review done along with a research on the design, simulation and control of a robot for use in upper-limb rehabilitation after stroke. Implications for Rehabilitation: Reviewing common terms in rehabilitation of upper limb using robots Reviewing rehabilitation robots built up to date Reviewing clinical outcomes of the mentioned rehabilitation robots